Problematika Pendidikan Agama Islam di Sekolah Umum Tingkat SMA - Annuriana Tsalitsa; Siti Nurrahayu Putri; Lusi Rahmawati; Nur Azlina; Ulya Fawaida (Tarbawiyah Jurnal Ilmiah Pendidikan, 2020)
This article describes the problems of Islamic religious education high school level public schools. The formulation of the issues raised is 1) What are the problems of Islamic religious education (PAI) found in high school level public schools 2) How are the solutions to overcome the problems of learning Islamic religious education (PAI) in public schools at the high school level. This research method is qualitative research using a literature study method, namely by displaying scientific reasoning arguments. The problems of PAI in high school level public schools include low interest learning learners in the PAI learning, lack of time allocation, problems in educators, problem in students, problem in facilities and infrastructure, the problem in PAI learning methods, and problem in learning evaluation. Meanwhile, solutions to overcome these problems, including replacing professional teachers, finding PAI teachers who are professional in their fields, every educator is included in events such as seminars, providing facilities and infrastructure for the implementation of sufficient Islamic religious teaching practices, educators must master various learning methods so that students easily understand the material delivered, increase the number of PAI teachers, and develop a learning evaluation system where the emphasis is on self-evaluation.